Advanced genetic therapies for the treatment of Rett syndrome: state of the art and future perspectives - Palmieri, Michela; Pozzer, Diego; Landsberger, Nicoletta (Frontiers in Neuroscience, 2023)
Loss and gain of functions mutations in the X-linked MECP2 (methyl-CpG-binding protein 2) gene are responsible for a set of generally severe neurological disorders that can affect both genders. In particular, Mecp2 deficiency is mainly associated with Rett syndrome (RTT) in girls, while duplication of the MECP2 gene leads, mainly in boys, to the MECP2 duplication syndrome (MDS). No cure is currently available for MECP2 related disorders. However, several studies have reported that by re-expressing the wild-type gene is possible to restore defective phenotypes of Mecp2 null animals. This proof of principle endorsed many laboratories to search for novel therapeutic strategies to cure RTT. Besides pharmacological approaches aimed at modulating MeCP2-downstream pathways, genetic targeting of MECP2 or its transcript have been largely proposed. Remarkably, two studies focused on augmentative gene therapy were recently approved for clinical trials. Both use molecular strategies to well-control gene dosage. Notably, the recent development of genome editing technologies has opened an alternative way to specifically target MECP2 without altering its physiological levels. Other attractive approaches exclusively applicable for nonsense mutations are the translational read-through (TR) and t-RNA suppressor therapy. Reactivation of the MECP2 locus on the silent X chromosome represents another valid choice for the disease. In this article, we intend to review the most recent genetic interventions for the treatment of RTT, describing the current state of the art, and the related advantages and concerns. We will also discuss the possible application of other advanced therapies, based on molecular delivery through nanoparticles, already proposed for other neurological disorders but still not tested in RTT.